빛간섭단층촬영기와 가변각막보정 주사레이저편광측정기의 국소 망막신경섬유층결손 발견능력의 비교 - 유영철; Young Cheol Yoo; 박기호; Ki Ho Park (Daihan angwa haghoi jabji, 2008)
목적: 빛간섭단층촬영기(Stratus OCT)와 가변각막보정 주사레이저편광측정기(GDx VCC)의 국소 망막신경섬유층 결손을 발견해내는 능력을 비교해 보고자 하였다. 대상과 방법: 정상인 36명과 국소 망막신경섬유층 결손을 보인 50명을 대상으로 한쪽 눈만을 선정하였다. 망막신경섬유층 사진을 기준으로 Stratus OCT와 GDx VCC의 국소 망막신경섬유층 결손 발견능력을 비교하기 위하여 민감도, 특이도, area under the receiver operating characteristic curve (AUC)를 계산하였다. 결과: Stratus OCT의 민감도(78.6%), 특이도(94.4%), AUC (0.872)는 GDx VCC의 83.3%, 94.4%, 0.882와 유의한 차이가 없었다(각각 p=0.75, 1.00, 0.84). 그러나, Stratus OCT의 위쪽 국소 결손에 대한 민감도(64.0%)는 아래쪽 결손에 대한 민감도(84.8%)보다 낮았다(p=0.02). 결론: Stratus OCT와 GDx VCC는 국소 망막신경섬유층 결손을 발견하는데 있어서 중등도의 민감도와 높은 특이도를 보였으며, 두 장비간의 진단능력에 유의한 차이를 보이지 않았다. <한안지 49(6):942-950, 2008> Purpose: To compare the abilities of optical coherence tomography (Stratus OCT) and scanning laser polarimetry with variable corneal compensation (GDx VCC) in detecting localized retinal nerve fiber layer (RNFL) defects of red free photography Methods: Thirty six normal subject and 50 patients with localized RNFL defects were included in this study. Only one eye per subject was considered. The peripapillary RNFL was divided into 12 clock-hour sectors and localized RNFL defects were evaluated in these 12 sectors. To compare the diagnostic performance of Stratus OCT and GDx VCC based on the findings of red-free photography, we calculated the sensitivity, specificity, and area under the receiver operating characteristic curve (AUC) of each analyzer using a criterion of 1≥clock hours abnormal at the <5% level. Results: The sensitivity (78.6%), specificity (94.4%), and AUC (0.872) of Stratus OCT were not significantly different from those of GDx VCC (83.3%, 94.4%, and 0.882, respectively) (McNemar test, p=0.75, 1.00, and 0.82, respectively). However, the sensitivity (64.0%) of Stratus OCT for superior RNFL defect was significantly lower than that (84.8%) for inferior defect (Fisher`s exact test, p=0.02). Conclusions: The sensitivity of the sector average of Stratus OCT and the deviation map of GDx VCC were fair in discriminating localized RNFL defects, and the specificity of those were excellent. In addition, the diagnostic performance was not significantly different between two analyzers. J Korean Ophthalmol Soc 49(6):942-950, 2008